Studi Kebijakan Pengembangan Kawasan Pangandaran Sebagai Kawasan Strategis Pariwisata Nasional - Sutadi, Tedi; Marsongko, Eka Paramita (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2017)
Pangandaran is a tourism destination has an important role in regional development at national, regional and local level. This is evident from the various policies, rules, and plans established and organized as a reference in the development of Pangandaran tourism. The development of tourism in this region is not only important for the tourism sector itself but more than that tourism development is expected to improve the welfare of society and reinforce the position of the region as a region and priority can improve the economy of the wider region. Development of tourism, products and tourism market, Pangandaran is well known both national and international levels. The appeal of the beach as the main product area is a pull factor for this region. However, the development of tourism products in the region is still not well managed and potential than the beach has not been fully developed as a supporter of the appeal.